Orienter et s’orienter vers l’enseignement supérieur dans un contexte de changement des politiques éducatives : incertitudes, choix, inégalités - Carole Daverne-Bailly; Claudie Bobineau (Éducation et Socialisation)
Through the careful consideration of the links between the high school reform and the ORE Act (2018), we show how the measures set up by the high schools for counselling their students on the path to higher education vary from one place to another in accordance with the top priorities set by every board of education. These measures activate especially some organizational levers, the commitment of teachers being hampered by many difficulties. The way the high school students do understand them differ as well according to their capability (socially constructed) to envision both their future and their studies. Our findings, based on 34 interviews, 369 questionnaires and 13 debates, underline how difficult it is to reduce the inequalities in the field of guidance on the way to higher education.